Business Potential of Post-Harvest Processing of Robusta Coffee in Jangkat Village, Merangin District - Dhio Wira Alanda; Raden Aswin Rahadi (UniSadhuGuna Business School, 2023)
Jangkat coffee or Merangin Robusta coffee is a variety of Robusta coffee that is one of the leading commodities from the highlands of Merangin district, Jambi province. Jangkat robusta coffee has high potential because it already has its own geographical indication area and has a very good taste score if proper post-harvest processing is carried out. There is huge potential to develop business by investing in post-harvest production of Robusta coffee greenbeans due to the large availability of raw materials there and also very few other companies engaged in the post-harvest coffee production processing industry in the area. Companies that want to invest in this area are expected to create value and profit by adhering to coffee certification and traceability standards and selling to business-to-business customers and this can be done by providing education to coffee farmers.